An Analysis of ICD Coding. (July 2014) - Liu Ling, Xi; Xiao Xiao, Lan
Abstract Objective. To explore issues relating to inaccurate coding in the classification of diseases related to poisoning, and to discuss the solutions. Methods. The current case management information system in the hospital was used to search for the classification of diseases related to poisoning during 2012 and 2013. The original medical records were compared with the results given by the system, followed by analyses of incorrect coding. Results. During the study period, the frequency of incorrect coding and additional coding was 14.7% and 32.4%, respectively. Conclusion. Staff in charge of disease coding should regularly examine the quality of data coded in the system, and a QC system should be added into the system to ensure its accuracy.